Rediscovery of the holotype of Tetragonopterus vittatus Castelnau 1855, a senior synonym of Moenkhausia doceana (Steindachner 1887) (Characiformes: Characidae) - Silva, Priscilla Caroline; Malabarba, Luiz Roberto (Zootaxa, 2016)
The description of Tetragonopterus vittatus presented by Francis L. Castelnau (1855) was very concise and apparently based on a single specimen (not explicitly stated in the text, but deducible according to the single counts for the meristic data presented in the description). The type locality is recorded simply as "Bahia", with no specification of the drainage or nearby city. The existence of type specimens has been considered unknown (Lima et al., 2003; Eschmeyer & Fricke, 2015; Lucena & Soares, 2016), and have not been mentioned in published catalogues for type specimens of MNHN (e.g. Bertin, 1948).